Generating Hexahedral Mesh for Wire-wrapped Fuel Assembly With RBF Mesh Deformation Method - Wang, X. A.; Zhang, Dalin; Wang, Mingjun; Liu, Yapeng; Zhou, Lei; Wang, Shibao; Liang, Yu; Tian, Wenxi; Qiu, Suizheng; Su, G. H. (Frontiers in Energy Research, 2021)
Fuel assemblies with wire spacer are widely used in Generation IV nuclear reactors core, and thermal-hydraulic modeling for these fuel assemblies is a key scientific subject. Taking advantage of the increased computational power, Computational Fluid Dynamic (CFD) method has been adopted for the investigation for wire-wrapped fuel assemblies. Due to the complexity of the geometry, most of the published researches are performed with large number tetrahedron or polyhedral cells. The simulation is quite costly and is generally limited to assemblies with small number of fuel pins. Coping with this problem, a hexahedron meshing strategy has been developed based on the radial basis function (RBF) theory in present paper. This strategy should be of some value for the modeling for the wire-wrapped fuel assemblies in real nuclear reactor core with large number of fuel pins. To validate this strategy, two experiments are simulated and detailed parameter distributions within the bundle has been compared including the pressure distribution and the temperature distribution. Good agreements have been achieved between the simulation results and the experimental results.